Scrutiny of melting rate of phase change material in a four petals cavity with internal branch fins under magnetic field - Farahani, Somayeh Davoodabadi; Farahani, Amir Davoodabadi; Mamoei, Amirhossein Jazari; Öztop, Hakan Fehmi (Elsevier, 2023)
This paper attempts to conduct the numerical simulation of the behavior of a phase change material (PCM) in a four petals enclosure with internal fins. The enthalpy-porosity method was used to simulate the thawing process. Two new enclosures with the different arrangements of the fins have been considered. The simulation results for the new finned geometries have been compared with those of the simple double-tube geometry. The effects of fin length (FL), angle between the fins (ABF), non-uniform magnetic field, Stefan number on the PCM melting process (PCM-MP) have been inspected. Results display that the average liquid fraction for new no-fin geometries has increased by about 14% compared to the simple double-tube. In both storage enclosures, the PCM-MP has increased by enhancing FL and falling ABF. ABF = 40 degrees is about 18.7% higher melting performance. Also, the use of non-uniform magnetic field and boosting its power improves the PCM-MP about 10%. Increasing Stefan number augments the PCM-MP by about 15%. The material of the fins has a momentous result on the PCM-MP.
Keywords: Melting; PCM; Four petals cavity; Branch fins; Non -uniform magnetic field